Local anesthetic pain catheters to reduce opioid use in massive weight loss patients undergoing abdominoplasty: A comparative study. Issue 4 (April 2020) - Giordano, Salvatore; Uusalo, Panu; Oranges, Carlo M.; di Summa, Pietro G.; Lankinen, Petteri
Summary: Background: Abdominoplasty is a common procedure for anatomical restoration of the lower abdominal skin, with a continuously increasing annual number of procedures performed. The significance of postoperative pain management is of crucial importance from a patient's perspective and to ensure the achievement of the aimed clinical outcome. We evaluated the efficacy of local pain pump catheters (PPCs) on massive weight loss patients undergoing body-contouring abdominoplasty. Methods: Primary abdominoplasty procedures after massive weight loss performed from 2009 to 2014 were retrospectively reviewed. The patients were divided into two groups according to the use of the PPC. The primary outcome measure was the amount of opioid use calculated as morphine equivalents. The secondary outcome measures were the length of hospital stay (LOS) and early postoperative complications within 30 days of surgery. Results: A total of 61 patients were included in the study: 24 patients in the PPC group and 37 patients in the conventional abdominoplasty analgesia (CAA) group. No significant differences between the study groups were found with regard to demographics, operative time, and resection weight. A significantly decreased use of opioids was observed after using PPC versus control (14.0 ± 13.9 mg vs. 74.6 ± 73.3 mg, p < 0.001). Similarly, the LOS was shorter in the PPC group (3.1 ± 1.1 days vs. 3.8 ± 1.0 days, p = 0.023). There was a similar rate of complications in both groups (45.8% vs. 40.5%, p = 0.622). The most common complication was seroma formation (25.0% vs. 18.5%, p = 0.315). Conclusion: The use of local anesthetic pain catheters in abdominoplasty may be associated with a decreased use of opioids and might result in a shorter hospital stay on massive weight loss patients. Further studies are needed to validate this treatment modality.